2022
DOI: 10.3390/molecules27041359
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Color of Rosé Wines Using Polyphenol-Targeted Metabolomics

Abstract: The color of rosé wines is extremely diverse and a key element in their marketing. It is due to the presence of anthocyanins and of additional pigments derived from them and from other wine constituents. To explore the pigment composition and determine its links with color, 268 commercial rosé wines were analysed. The concentration of 125 polyphenolic compounds was determined by a targeted metabolomics approach using ultra high-performance liquid chromatography coupled to triple quadrupole mass spectrometry (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The positive trend in international preferences could offer producers an opportunity to improve the communication and attractiveness of rosé wine to the domestic market. To an even greater extent than white and red wines, the color of rosé plays a key role in defining the perceived quality of the product, which can range from pale rosé nuances to orange ones, as in wines whose color is referred to as onion skin tones [2]. The phenolic class of anthocyanins and the resulting pigments are primarily responsible for the color of red and rosé wines [3].…”
Section: Introductionmentioning
confidence: 99%
“…The positive trend in international preferences could offer producers an opportunity to improve the communication and attractiveness of rosé wine to the domestic market. To an even greater extent than white and red wines, the color of rosé plays a key role in defining the perceived quality of the product, which can range from pale rosé nuances to orange ones, as in wines whose color is referred to as onion skin tones [2]. The phenolic class of anthocyanins and the resulting pigments are primarily responsible for the color of red and rosé wines [3].…”
Section: Introductionmentioning
confidence: 99%
“…Peng Q. et al used gas chromatography (GC)-flash electronic nose in combination with chemometrics to successfully differentiate between Chinese Tongshan kaoliang spirits from different geographical origins [ 22 ]. Leborgne C. et al reported the color of rosé wines by polyphenol-targeted metabolomics, which can also be applied to identify the varietal and geographical origin of the wines [ 23 ]. Moreira N et al used PFBHA derivatization combined with HS-SPME-GC-MS to determine the content of carbonyl compounds in various aged port wines, and to differentiate among them [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Color is essential for the quality of rosé wines and a major driver of consumers' purchase as they are usually sold in clear glass bottles [1]. Rosé wines are extremely diverse, covering a wide range of intensities and nuances, reflecting large differences in pigment compositions [2]. Indeed, rosé wines pigments contain phenolic compounds [2,3], including red anthocyanin pigments extracted from grapes and derived pigments formed during wine making through reactions of anthocyanins with other phenolic compounds and with wine metabolites such as acetaldehyde and pyruvic acid [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rosé wines are extremely diverse, covering a wide range of intensities and nuances, reflecting large differences in pigment compositions [2]. Indeed, rosé wines pigments contain phenolic compounds [2,3], including red anthocyanin pigments extracted from grapes and derived pigments formed during wine making through reactions of anthocyanins with other phenolic compounds and with wine metabolites such as acetaldehyde and pyruvic acid [4]. In addition, the rosé wine-making process, involving pressing before fermentation, i.e., when grape polyphenoloxidase is highly active, enables the enzymatic oxidation of hydroxycinnamic acids and flavan-3-ols, potentially leading to browning [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation